Teaching and Learning Portuguese as a Second Language for Deaf Students: Reflections on Teaching Practices in An Inclusive Context - Valadão, Michelle Nave; Carlos Antonio Jacinto (European Journal of Social Science Education and Research, 2019)
In Brazil, according to the principles of bilingualism, the process of teaching written Portuguese to deaf people should be based on methodologies used to teach a second language (L2). Also, the teaching method should be developed from experiences with the Brazilian Sign Language (LIBRAS). On that account, the present study investigated the teaching-learning process of the written Portuguese experienced by a deaf student in an inclusive class. A qualitative, descriptive and exploratory research was conducted. As for collecting data, three methods were explored: participant observation, field diary and document analysis. The results indicated that in the aforementioned process, LIBRAS was not appreciated as a first language (L1). They also showed that no Portuguese language teaching methodology based on a L2 was used. Thus, we concluded that the methods used for teaching the written language in the inclusive situation did not meet the principals of bilingual education and did not embody all the linguistic and cultural singularities of the deaf student.
Keywords: Teaching and learning Portuguese, Brazilian Sign Language (LIBRAS); Deafness.